(3RhGd GdTc hGdGdJHGS YeG aj bdhH HYV GdfGSs - (3CMeO Hf GdTjN eMeO GdehShes
(3ChdgG (B:s
(3GdMeO ddg GdPi HMeOg JJe GdUGdMGJ hHeYQaJg hWGYJg Jced LejY GdNjQGJ s
(3BNQgG (B:s
(3hCQLhG Cf jchf ebHhdG YfO GdhGbajf Ydjg ef GdSGOGJ GdcQGe hGdSdGe Ydi GdbGQF hGdeSJeY ef LejY GdCfGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B7(3C (B- (3U(B11(3Cs
(3YQa ajg HGdSjGSI GdaQfSjI fMh CgGdi GdLRGFQ hPdc ai Chd YgO GdEMJdGd GdaQfSis
(3agQSJ GdQHGW (B:(3L(B2 (3U`(B149s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B225 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B149 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1458(3O(B) s
Keywords: (3GdJGQjNs